MATERNAL DEATH DETERMINANT AND HEALTH SERVICE DELIVERY DURING COVID-19: WHAT'S THE DIFFERENCE? Determinan Kematian Ibu dan Pelayanan Kesehatan Selama Pandemi COVID-19: Adakah Perbedaan? - Moch Jazil Ainul Yaqin; Danik Iga Prasiska; Nur Aini Fatah (Jurnal Berkala Epidemiologi, 2023)
Background: The COVID-19 pandemic has provided a new challenge for the delivery of health system in Indonesia. Maternal health services were no exception, as the reduction in antenatal unscheduled home visits were the main issues found in maternal health service disruption during the COVID-19 pandemic. In the last few decades, Indonesia has adopted a range of health strategies to reduce maternal mortality rates. Nganjuk is one of the regencies that enforce the reduction of maternal mortality, which successfully reducing maternal mortality rates from 212 per 100.000 live births in 2010 to 57 per 100.000 live births in 2018. With the emergence of COVID-19, the health system's capacity and access are once again being shaken. Purpose: This research aimed to analyze the determinants of maternal death before the COVID-19 pandemic situation and during the COVID-19 pandemic. Method: This type of research is non-reactive research using secondary data from maternal mortality reports, Nganjuk Regional Health Office. Analysis was carried out with a chi-Square test using Statistical Package for the Social Sciences (SPSS) version 26.0. Results: A significant increase in maternal deaths (85.29%) was observed during the COVID-19 pandemic. Determinants of maternal death, such as the age of the mother (p<0.00), number of pregnancies (p<0.00), period of death (p=0.02), healthcare referral (p=0.01), and cause of death (p<0.00) showed a significant increase during COVID-19. Conclusion: COVID-19 pandemic contributed to the increase in maternal deaths in Nganjuk Regency. This study has implications for the priority setting in policy development and implementation at reducing maternal mortality.